The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/hepr.12974
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus‐related symptoms, but not quality of life, were improved by treatment with direct‐acting antivirals

Abstract: Treatment with DAAs eliminated HCV-RNA and improved most symptoms, but QOL did not recover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…8,14 HRQoL is currently assessed in western and Asian populations but rarely in Africa as a tool for the determination of the beneficial effect of antiviral treatment on HRQoL in patients with CHB. 5,13 Our study demonstrated that Black African patients with CHB receiving antiviral treatment have elicited probably psychological distress as reported by Ichikawa et al, in patients with chronic hepatitis C. 35 Furthermore, we confirmed as other previous publications that subjects having subsidies experienced better HRQoL whereas comorbidities diminish HRQoL as did CHB in comparison with control subjects in our study. 4,5,9,19,36 We also demonstrated that BMI was positively correlated with good HRQoL in black Africans probably since our patients were not under or overweighted.…”
Section: Discussionsupporting
confidence: 91%
“…8,14 HRQoL is currently assessed in western and Asian populations but rarely in Africa as a tool for the determination of the beneficial effect of antiviral treatment on HRQoL in patients with CHB. 5,13 Our study demonstrated that Black African patients with CHB receiving antiviral treatment have elicited probably psychological distress as reported by Ichikawa et al, in patients with chronic hepatitis C. 35 Furthermore, we confirmed as other previous publications that subjects having subsidies experienced better HRQoL whereas comorbidities diminish HRQoL as did CHB in comparison with control subjects in our study. 4,5,9,19,36 We also demonstrated that BMI was positively correlated with good HRQoL in black Africans probably since our patients were not under or overweighted.…”
Section: Discussionsupporting
confidence: 91%
“…In general population, two different reports describe improvements in QOL after DAA treatment [ 19 , 26 ]. These data, quite surprisingly, were not confirmed by Ichikawa et al in a cohort of cirrhotic patients that showed significant ameliorations in many cirrhosis-related symptoms after treatment [ 27 ]. Probably, the life expectancy of cirrhotic patients (compared to transplant recipients) and, mostly, the degree of hepatic impairment have conditioned this result: in fact, it may require several years after relief from liver-related symptoms for an effect on QOL to become apparent [ 27 ].…”
Section: Discussionmentioning
confidence: 81%
“…Patients reported experiencing significantly fewer depressive symptoms at 12 weeks post treatment compared to baseline (as measured by the Montgomery Åsberg Depression Rating Scale) . Other studies have highlighted significant improvements in cirrhotic symptoms (Cirrhosis‐Related Symptom Score), psychological distress (Kessler‐6 Score), sleep quality (Pittsburgh Sleep Quality Index) and cognitive function post DAA treatment compared to baseline …”
Section: Measuring the Impact Of Daasmentioning
confidence: 96%
“…54 Other studies have highlighted significant improvements in cirrhotic symptoms (Cirrhosis-Related Symptom Score), psychological distress (Kessler-6 Score), sleep quality (Pittsburgh Sleep Quality Index) and cognitive function post DAA treatment compared to baseline. 55,56 Recent data from placebo-controlled clinical trials underscores the association between viral clearance and improvements in patient-reported outcomes. 57 Thus, reaping these extra-hepatic benefits of treatment may be contingent on viral eradication and good adherence to treatment.…”
Section: Studies Reporting Associations Between Viral Clearance and Imentioning
confidence: 99%